Packaging attributes that affect consumer buying behavior on generic product in Aeon Big Sutera Utama / Suhaili Md Tarmudi and Muhammad Amnan Ruslan - Md Tarmudi, Suhaili; Ruslan, Muhammad Amnan (2014)
This research is mainly focus on the packaging elements that influence consumers buying behavior towards Aeon Big house brand. The objective of this study is to determine the level of consumer buying behavior and to study the affect of packaging attributes (design, colour, material, labeling) on consumers buying behavior at Aeon Big Sutera Utama, Johor Bahru. From the result of this research will shows that whether the respondents agree or disagree that packaging attributes such as design, colour, material and labeling does influence their buying behavior. Therefore, this research has been set up and been carried out to test and reveal the answer of this research objectives. Since the data of consumers in Aeon Big are private and confidential, a convenience sampling method has been used to distribute the questionnaire. A total of 20 pilot test surveys and 300 questionnaires have been distributed where from 300 distributed questionnaire, only 285 been able to collect back and 263 has passed the data cleaning process. From the 263 questionnaire obtained, an analysis has been conducted by using SPSS system version 20 and SPSS system version 22 to carry out the data analysis and to find out whether the earlier hypothesis are supported or not and whether the research objectives has been achieved or not.